Diagnóstico da logística reversa na cadeia de suprimentos de alimentos processados no oeste paranaense - Chaves, Gisele de Lorena Diniz (2005)
This study analyzes reverse logistics in the processed food supply chain of the State of Paraná?s West region to systemize and identify its practices and strategic functions The relation between the agents: industry and supermarket of this chain is shown The gathered information and critical points minimize the problem of lack of data related to the reverse processes and allow the improvement and development of the activity Therefore the research method was the descriptive and applied survey It was used an interview structured by a questionnaire covering a population of 25 companies of the State of Paraná?s food industry and supermarkets for data collection After statistical analysis of the data it was pointed out as main results: a) the totality of food industries and the majority of the supermarkets analyzed manage returns but the responsibility for the returns is of the manufacturer; b) the nature of reverse logistics tends to be more conservative in the food industries and more liberal among supermarkets; c) the main strategic role reverse logistics plays in enterprises both in the industrial and retail sectors is that of satisfying customers; d) the main processes adopted by food industries are the disposal and recycling of returns while by supermarkets are the returns? disposal and donation; e) in general companies point out the inexistence of barriers for reverse logistics despite the absence of a measurement of the costs involved in the activity It is concluded that the relationship industry-supermarket is that of the type win-win in which both sectors have each well defined responsibilities and roles in the reverse logistics process and divide the inherent costs in this process It was noticed that the absence of specific and standardized procedures and the disinterest in improving the reverse flows management were present in most of the companies characterizing a deficiency in planning and managing the reverse logistics network Besides the lack of indicators that prove the activity?s cost/benefit relation contributes to the activity not to be considered a strategic element by the companies of this sector Reverse logistics should be reviewed and improved so that the service standards offered to customers can rise and be converted in competitive advantage for the companies